LIMITED FACE-TO-FACE LEARNING MANAGEMENT DURING THE COVID-19 PANDEMIC - Ainun Amaliya Paramita; Farid Setiawan; Retno Palupi; Rijal Khoirul Anam (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2021)
This study aims to understand the management of learning in schools at SD Negeri Caturtunggal 3, Depok, Sleman, Yogyakarta Special Region, during the Limited Face-to-Face Learning (PTMT) was carried out during the Covid-19 pandemic. The method used in this research is qualitative. The results showed that the limited face-to-face learning carried out after the previous learning was done online, there were several obstacles that the students strongly dominated at the beginning of the learning implementation. Limited face-to-face learning has obstacles. Namely, many students are confused when invited to icebreaking. Students are still adjusting to the learning, and the reality of student understanding seen from the assessment during online learning and then implemented in a limited manner is very different. Although at the beginning of the implementation of limited face-to-face learning, there were still obstacles, SD Negeri Caturtunggal 3 was able to prepare and develop sound strategies to manage limited face-to-face learning to anticipate unwanted things.